Factors Affecting Mother Behavior in Complementary Feeding Stunting Age 6-24 Months in Sidoarjo Regency - Anisa Anisa; Mochammad Bagus Qomaruddin; Mohammad Zainal Fatah (Health Notions, 2018)
Stunting is a growth disorder, which is often encountered in children less than 24 months. The prevalence of under-five stunting in East Java in 2016 was 26.1% and the prevalence of under-five stunting in Sidoarjo Regency in 2016 was 21.9%. Stunting events at 6-24 months are associated with many factors. The purpose of this study was to analyze the factors that influence the behavior of mothers in the feeding practice in the Health Office of Sidoarjo Regency. The type of this research was observational analytic with cross sectional study design. The subjects of the study were 158 mothers with stunting children aged 6-24 months. Selection of research subjects using probability sampling technique. The status of stunting was measured by body length according to age. Based on the result of Binary Logistic Regression, it is obtained that there was influence of self efficacy on expected outcome with p-value = 0.0001 and there was influence of self efficacy on intention with significant p = 0.021. Keywords: Complementary feeding, Stunting, Self efficacy, Outcome expectancies, Intention